An ocean apart: meteorology and the elusive observatories of British Malaya - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2023)
Throughout the late nineteenth century, the British established observatories, meteorological posts, and stations across their burgeoning empire. These institutions and their networks were part of a global endeavor to map and understand the weather by collating vast quantities of data, and, it has been argued, they were also emblematic of imperial prowess and reach. In the Straits Settlements, however, unlike almost every other British colony, observatories came and went, and meteorology lacked central coordination and funding. This essay explores the reasons behind this erratic and often elusive meteorological provision and interest. It argues that contemporary perceptions of the Straits Settlements climate as stable and lacking in seasonality or extremes led to a lack of interest in meteorology at local and international levels. This resulted in a bureaucratic disinclination to invest in the science, despite its major value to agricultural productivity, the linchpin of the economy. In so doing, this study interrogates the absence of formal provision or structure, focusing instead on the diluted mechanisms and sites that kept a meteorological narrative alive until its formal institutionalization in Singapore in 1929.